Tunable temperature-dependent THz photonic bandgaps and localization mode engineering in 1D periodic and quasi-periodic structures with graded-index materials and InSb - Singh B.K.; Pandey P.C. (My University, 2025)
We present the tunability of terahertz (THz) photonic bandgaps and localization modes in one-dimensional (1D) periodic and quasi-periodic structures based on alternating layers of graded-index materials and InSb. These configurations show that operation frequencies of photonic bands and localization modes can be tuned by controlling temperature, structural and grading parameters, grading profiles, and different quasi-periodic arrangements. The number of photonic bands and localization modes can also be modulated with layer thickness and quasi-periodic arrangements. Changes in the grouping of the materials considered also modulate the operation frequencies of photonic bands and localization modes in quasi-periodic structures. Results can be implemented to design thermo-tunable THz filters, reflectors, sensors, etc. © 2018 Optical Society of America.